Rationalizing Islam’s prohibition of drawing images and erecting statues of humans - Omer, Spahic (IIUMToday, 2019)
Islam categorically prohibits drawing images and erecting statues of humans. The matter pertains as much to fiqh (Islamic jurisprudence) as ‘aqidah (Islamic belief system). There are many authentic hadiths (traditions) of the Prophet (peace and blessings be upon him) that testify to this. According to those hadiths, the image makers are cursed; they are called some of the most evil creation; they will be most severely punished on the Day of Judgment; they will be punished until they breathe life into their “creations”, but they will never be able to do that; and the angels do not enter houses in which there are statues (Sahih al-Bukhari and Sahih Muslim). What are the reasons for this unequivocal prohibition? By and large, human images and statues are produced in the name of art, in its two main classical branches: painting and sculpture. They are meant to be appreciated for their beauty, meaning and emotional power, predicated on an artist’s imagination, resourcefulness, conceptual ideas and skills. Authentic art is a process of discovering in life and nature their essence, which is meta-physical. It is furthermore ontological, dealing with the fundamental nature of being. That essence is then given a physical form most appropriate for it. The nearer the visible object is to the essence, the more beautiful it is. Art, therefore, is the trickiest and most challenging thing, bordering on the impossible. It is an attempt to rationalize, in essence, the irrationalizable and represent the unrepresentable. Needless to say that authentic art is not the imitation of created nature. A photographic representation, which reproduces the object as it is, may be valuable for illustration or documentation, for the establishment of identity. As a work of art, it is worthless.